Autologous breast reconstruction using the immediately lipofilled extended latissimus dorsi flap. Issue 2 (February 2018) - Johns, N.; Fairbairn, N.; Trail, M.; Ewing, A.; Yong, L.; Raine, C.; Dixon, J.M.
Summary: Background: The latissimus dorsi flap is a popular choice for autologous breast reconstruction. To dramatically improve volume, we report our experience of using the immediately lipofilled extended latissimus dorsi (ELD) flap and show it as a valid option for autologous breast reconstruction. Methods: Patients undergoing the procedure between December 2013 and June 2016 were included. Demographic, clinical and operative factors were analysed, together with in-hospital morbidity and duration of postoperative hospital stay. Results: A total of 71 ELD flaps with immediate lipofilling were performed. Forty-five reconstructions were immediate and the remaining 26 delayed. Median (range) volume of autologous fat injected immediately was 171 ml (40–630 ml). Contralateral reductions were performed in 25 patients with the median reduction volume 185 g (89–683 g). Median duration of admission was 6.5 (3–18) days and patients were followed up for 12 months (1–37). Three total flap failures occurred and had to be excised (4%). One haematoma occurred requiring drainage (1%). Signs of infection requiring intravenous antibiotics occurred in five patients (7%). In 5 patients wound dehiscence occurred, and only two of these required resuturing (3%). In total, 7 patients developed a seroma requiring repeated drainage (10%). Three reconstructions experienced mild mastectomy flap necrosis with no needing reoperation (4%). Conclusions: Our experience represents the largest series to date and shows that in carefully selected patients the technique is safe, can avoid the requirement for implants, and has the potential to streamline the reconstructive journey.